Financiamento das aç\~oes e serviços públicos de saúde no Brasil: Um retrato das desigualdades regionais do período 2010-2022 - Sérgio F. Piola; Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This text continues previous studies, carried out at Ipea, which analyze the spending of the three levels of government in financing the Unified Health System (SUS). Taking the period from 2010 to 2022 as a basis, the study analyzes the behavior of spending on health actions and services (ASPS) by the Union, states, the Federal District and municipalities in the shared financing of the SUS. The work shows the effects of measures to contain public spending (EC no 95/2016) and combat the Covid-19 pandemic on public financing of the system. As in previous studies, this text shows the evolution and regionalized distribution of total spending, specifies the evolution of spending in different spheres of Government, with emphasis on federal spending by region and federative unit. It presents and discusses the emergence, from 2015, of the transfer of federal resources via parliamentary amendments (EPs) of different types and discusses the problems arising from the growing volume of resources involved in this type of resource allocation.
Keywords: H51; 330; healthcare financing.; health care rationing; equity in the resource allocation; health expenditures; public expenditures on health; Unified Health System